2012
DOI: 10.1371/journal.pone.0038236
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Language Learning by Robots: The Transition from Babbling to Word Forms

Abstract: The advent of humanoid robots has enabled a new approach to investigating the acquisition of language, and we report on the development of robots able to acquire rudimentary linguistic skills. Our work focuses on early stages analogous to some characteristics of a human child of about 6 to 14 months, the transition from babbling to first word forms. We investigate one mechanism among many that may contribute to this process, a key factor being the sensitivity of learners to the statistical distribution of ling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…This¯nding is consistent with those of prior studies using RALL on general English pro¯ciency or similar studies. 3,13,14,[28][29][30][31][32][33] However, this study is more in line with Hyun et al 29 who worked with preschoolers' vocabulary using RALL and found their improvement was signi¯cantly better than the CALL group.…”
Section: Discussionsupporting
confidence: 84%
“…This¯nding is consistent with those of prior studies using RALL on general English pro¯ciency or similar studies. 3,13,14,[28][29][30][31][32][33] However, this study is more in line with Hyun et al 29 who worked with preschoolers' vocabulary using RALL and found their improvement was signi¯cantly better than the CALL group.…”
Section: Discussionsupporting
confidence: 84%
“…First, the task was inspired from similar developmental psychology experiments showing how young children learn to associate visual objects with novel words through child-parent social interactions [Baldwin 1993; Estes, Evans, Alibali and Saffran 2007; Yu and Smith 2012]. Second, there is a trend in developmental robotics that users teach robots human languages through human-robot interactions [Lyon, Nehaniv and Saunders 2012; Marocco, Cangelosi, Fischer and Belpaeme 2010; Tanaka and Matsuzoe 2012; Xu, et al 2013; Yu, et al 2010]. Moreover, this joint task naturally engaged participants to interact with the robot without any constraint on what they had to do or what they had to say.…”
Section: Methodsmentioning
confidence: 99%
“…In this case the hearer can often have a passive as well as an active role. Active listening occurs when a subject directs their attention to speech or other sounds, so humanoid robots acquiring linguistic skills through interaction with a human will typically be listening in an active mode [17]. On the other hand, auditory perception can be passive: a sleeping person can be woken by sounds, and some loud or incessant noise can be an unpleasant experience that the hearer cannot escape.…”
Section: Active Visual Processing and Passive Perception In Other Modmentioning
confidence: 99%
“…This highlights the point that orthographic transcripts of spontaneous speech may not be a close match to perceived sounds -a point that needs to be taken into account when research into, for instance, child language acquisition uses corpora of written transcripts of child directed speech. The observed fact that content words are more likely to have consistent phonemic structure is exploited in work simulating the learning of word forms by a humanoid robot which interacts with humans [17].…”
Section: The Perception Of Phonemesmentioning
confidence: 99%